Tourniquet modification of the associating liver partition and portal ligation for staged hepatectomy procedure. Issue 9 (19th June 2014) - Robles, R; Parrilla, P; López-Conesa, A; Brusadin, R; de la Peña, J; Fuster, M; García-López, J A; Hernández, E
Abstract: Background: In staged liver resections, associating liver partition and portal ligation for staged hepatectomy (ALPPS) achieves sufficient hypertrophy of the future liver remnant (FLR) in 7 days. This is based on portal vein ligation and transection, and on occlusion of intrahepatic collaterals. This article presents a new surgical technique for achieving rapid hypertrophy of the FLR, which also involves adding intrahepatic collateral occlusion to portal vein transection. Methods: Patients scheduled for two-stage liver resection for primary or secondary liver tumours, in whom the FLR was considered too small, were enrolled prospectively. In the first stage, a tourniquet was placed around the parenchymal transection line, and the right portal vein was ligated and cut (associating liver tourniquet and portal ligation for staged hepatectomy, ALTPS). The tourniquet was placed on the umbilical ligament if a staged right trisectionectomy was planned, and on Cantlie's line for staged right hepatectomy. Results: From September 2011, 22 ALTPS procedures were carried out (right trisectionectomy in 15, right hepatectomy in 7). Median FLR at 7 days increased from 410 to 700 ml (median increase 61 (range 33–189) per cent). The median duration of the first stage was 125 min and no patient received a blood transfusion. The median duration of the second stage was 150 min and five patients required a blood transfusion. Fourteen patients had complications, most frequently infected collections, and five patients developed postoperative liver failure. Two patients died. Conclusion: The ALTPS technique achieved adequate hypertrophy of the FLR after 7 days. It may provide a less aggressive modification of the ALPPS procedure. Abstract : Simplification of the ALPPS procedure